1999
DOI: 10.1161/01.res.85.8.707
|View full text |Cite
|
Sign up to set email alerts
|

A Novel K ATP Current in Cultured Neonatal Rat Atrial Appendage Cardiomyocytes

Abstract: The functional and pharmacological properties of ATP-sensitive K(+) (K(ATP)) channels were studied in primary cultured neonatal rat atrial appendage cardiomyocytes. Activation of a whole-cell inward rectifying K(+) current depended on the pipette ATP concentration and correlated with a membrane hyperpolarization close to the K(+) equilibrium potential. The K(ATP) current could be activated either spontaneously or by a hypotonic stretch of the membrane induced by lowering the osmolality of the bathing solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 44 publications
3
56
1
Order By: Relevance
“…In the immature rat heart, K ATP channel density is also high, but the single-channel conductance and the mean open time are the same as in the adult (2). Reports describing a smaller unitary conductance in neonatal rat atrium (4) suggested that there may be regional differences. The immature rat heart K ATP channel has a lower open probability, and the channels are much more sensitive to block by intracellular ATP (2,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the immature rat heart, K ATP channel density is also high, but the single-channel conductance and the mean open time are the same as in the adult (2). Reports describing a smaller unitary conductance in neonatal rat atrium (4) suggested that there may be regional differences. The immature rat heart K ATP channel has a lower open probability, and the channels are much more sensitive to block by intracellular ATP (2,5).…”
mentioning
confidence: 99%
“…In addition to these biophysical changes, there are reports that immature K ATP channels may have a different pharmacological profile. The neonatal atrial K ATP channel shows a unique functional and pharmacological profile resembling the pancreatic ␤ cell channel for its unusually high affinity for glibenclamide and diazoxide (4,5). These characteristics suggest that neonatal K ATP channels may differ in their molecular composition relative to the mature heart.…”
mentioning
confidence: 99%
“…7 D). Based on our results it seems very likely that heteromeric K ATP channels are formed in native cells coexpressing SUR1 and SUR2; this may explain the displayed current phenotypes, such as intermediate metabolic sensitivities and pharmacological profi les observed in such cells (Baron et al, 1999;Liss et al, 1999;Poitry et al, 2003;Yunoki et al, 2003). The physiological role of these heteromeric channels during metabolic stresses, as well as their responses to drugs such as sulfonylureas and potassium channel openers, remain to be established.…”
Section: Discussionmentioning
confidence: 77%
“…Contradictory to this study, several reports suggested/indicated that SUR1 and SUR2 can coassemble into functional channels. First, single K ATP channels obtained from rat atrial myocytes displayed both SUR1 and SUR2 properties (Baron et al, 1999). Second, three populations of dopaminergic neurons, expressing Kir6.2 with SUR1, SUR1+SUR2B, and SUR2B, displayed K ATP currents with high, intermediate, and low sensitivities, respectively, to tolbutamide and metabolic inhibition (Liss et al, 1999).…”
Section: S1-wt and S2-nd Subunits Readily Coassemble In A Random Mannermentioning
confidence: 99%
See 1 more Smart Citation